Effect of the polarity of KTa1−xNbxO3 on the dielectric performance of the KTN/PVDF nanocomposites. Issue 44 (13th July 2020) - Lin, Jiaqi; Li, Yang; Liu, Xinmei; Li, Yuanshuo; Zheng, Weijie; Yang, Wenlong
Abstract : KTa1− x Nb x O3 with different Ta/Nb ratios ( x = 0.15, 0.25, 0.5, 0.75, 0.85) were engineered and prepared by a facile hydrothermal synthesis method to acquire KTN nanoparticles with varied polarity. Abstract : KTa1− x Nb x O3 with different Ta/Nb ratios ( x = 0.15, 0.25, 0.5, 0.75, 0.85) were engineered and prepared by a facile hydrothermal synthesis method to acquire KTN nanoparticles with varied polarity. To investigate the effect of KTN filler with varied polarity on the dielectric performance of polymer matrix composites, KTN/PVDF films were fabricated. The experiment demonstrated the polarity of KTN affected the dielectric performance of the composites. KTa0.5 Nb0.5 O3 possesses larger polarity with permittivity of 3780 at 1 kHz due to its Curie temperature is closer to room temperature, which contributes 30 wt% doped KTa0.5 Nb0.5 O3 /PVDF composite achieving higher permittivity of 19.5 at 1 kHz than those of the others. Additionally, KTa0.75 Nb0.25 O3 /PVDF composite presents higher breakdown strength than those of the others with an E b value of 164 kV mm −1 when 20 wt% filler is doped. The significant improved dielectric performance by Ta/Nb ratio engineering has the potential of providing new insight on enhancing the energy storage in ceramic-polymer nanocomposites.